Penerapan Protokol RAMP dan Teknologi Analisis Kinerja untuk Peningkatan Performa Pemain Sepakbola Gumarang FC Medan - Asep Prima; Ardi Nusri; Reisy Tane; Yan Indra Siregar; Haris Kurniawan (Universitas Muhammadiyah Malang, 2026)
Purpose – The purpose of this community service is to improve physical readiness, minimize injuries, and enhance player evaluation quality at Gumarang FC Medan by applying the RAMP warm-up protocol, implementing structured trial management, and using ONCE Sport performance analysis technology. Design/methodology/approach – The activities included socialization, theoretical and practical training, and direct implementation of the RAMP protocol and ONCE Sport technology during training and trial matches. Data were collected using a Likert scale questionnaire and analyzed descriptively to assess coaches' perceptions of the program's effectiveness. Findings – The results show that coaches perceive the RAMP protocol as highly effective (mean 4.56), easy to implement (mean 4.38), and effective in improving physical readiness (mean 4.63) and reducing the risk of injury (mean 4.75). ONCE Sport technology was considered useful (mean 4.44), fairly easy to use (mean 4.13), and very helpful in evaluating players (mean 4.50). RAMP improved agility, speed, and endurance, and ONCE Sport provided objective, data-based evaluations. Originality/value – This community service integrated evidence-based warm-up protocols and performance analysis technology into local soccer clubs. It provides a model that can be replicated by clubs with limited resources to improve training quality and player evaluation.